2019
DOI: 10.1115/1.4042501
|View full text |Cite
|
Sign up to set email alerts
|

Lean-Burn Characteristics of a Heavy-Duty Diesel Engine Retrofitted to Natural-Gas Spark Ignition

Abstract: Increased utilization of natural gas (NG) in the transportation sector can decrease the use of petroleum-based fuels and reduced greenhouse gas emissions. Heavy-duty diesel engines retrofitted to NG spark ignition (SI) can achieve higher efficiencies and low NOX, CO, and hydrocarbon (HC) emissions when operated under lean-burn conditions. To investigate the SI lean-burn combustion phenomena in a bowl-in-piston combustion chamber, a conventional heavy-duty direct-injection CI engine was converted to SI operatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 30 publications
0
12
0
1
Order By: Relevance
“…a more evident second peak in the heat release rate) would appear if the operating conditions increased the separation between the fast- and slow-burning stages. 18,19 These results suggest that an approach to increase the thermal efficiency in such an engine is to optimize the flame propagation inside the bowl, which would decrease the duration of the first combustion stage and probably lower the unburned mass fraction inside the slow-burning region. Consequently, it is of interest to first improve the fundamental understanding of the lean-burn SI NG operation inside the piston bowl.…”
Section: Introductionmentioning
confidence: 97%
“…a more evident second peak in the heat release rate) would appear if the operating conditions increased the separation between the fast- and slow-burning stages. 18,19 These results suggest that an approach to increase the thermal efficiency in such an engine is to optimize the flame propagation inside the bowl, which would decrease the duration of the first combustion stage and probably lower the unburned mass fraction inside the slow-burning region. Consequently, it is of interest to first improve the fundamental understanding of the lean-burn SI NG operation inside the piston bowl.…”
Section: Introductionmentioning
confidence: 97%
“…For predicting knocking [45,46], the in-cylinder needs to be divided into at least two zones (the burnt zone and the unburnt zone or end-gas zone), in order to characterize the flame propagation and end-gas auto-ignition. Thus, the 0-D combustion models for knocking prediction are commonly associated with the cylinder volume division similarly to the two-zone models [47,48] and multi-zone models [49][50][51]. Xiang et al [47] proposed a two-zone model based on the Douaud-Eyzat correlation [37] to predict the knocking performance of the SI natural gas engines by assuming that the burnt and unburnt zones have a cylindrical shape.…”
Section: Introductionmentioning
confidence: 99%
“…As concluded from the discussed literature [44][45][46][47][48], a two-zone 0-D model could be an effective tool for the knocking behaviour analysis in NG engines as it is capable of characterising the end-gas zone temperature with the simplest combustion zone division. In addition, a 1-D model [56,57] could be employed for simulating the gas exchange process in order to improve the simulation accuracy of the entire engine cycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Weaver et al [11] reported that the roof-type head geometry in conventional SI engines is not optimal for lean combustion due to combustion instabilities and increased cycle-to-cycle variations. Consequently, gasoline engines with a roof-type head are more likely to be modified to NG stoichiometric operation [46,47]. In other words, the slow-burn geometry of conventional gasoline engines and NG's low laminar flame speed at lower equivalence ratio are not ideal to converting SI engines to NG lean burn operation.…”
Section: Natural Gas In Gasoline Enginesmentioning
confidence: 99%